Mobilizing a Global Response to Hepatitis : Lessons Learned from the HIV Movement - Taaffe, Jessica (Taylor and Francis, 2018)
Hepatitis caused by hepatitis B and C virus is increasingly becoming a significant global health threat, with widespread prevalence that may have severe disease and economic impacts in the future. Yet, preventative measures are not implemented universally and high costs of medicines limits treatment efforts. The global response to HIV/AIDS faced similar issues, but overcame them through a global movement that brought attention to the crisis and ultimately resulted in the creation and implementation of and access to better tools for HIV prevention and treatment. This also included effective policies and programs behind and supporting the movement. Such could be done for hepatitis, specifically using lessons from the HIV response. Here, we will discuss the current and potentially severe future burden of hepatitis globally, the challenges in addressing this epidemic, and how principles applied from the global HIV response can facilitate a successful and similar hepatitis movement.